La cançó de Santa Fe, text catalano-occità del segle XI. - CASANOVA, EMILI (Scripta)
The article consists of three parts: a first, on the state of the question of the territorial assignment of the Cançó; a second, making an exhaustive study, trying to demonstrate that the linguistic features of the Cançó of the eleventh century can all be Catalan as well as Occitan, and some only Catalan. After the study, it is concluded that the work composed first in Latin, with cultured roots, would be translated or adapted -or copied- in Catalan-Occitan in the Cerdanya-Conflent-Roussillon area, within the context of the Camino de Santiago. And a third, consisting of a new edition following the criteria of Our Classics in Catalan, unlike previous editions made in French fashion, which helps to read it better and to consider it Catalan.